Optimizing TACE for Hepatocellular Carcinoma: The Impact of Intra-Arterial Contrast Enhanced Ultrasound - Linda Galasso; Jacopo Iaccarino; Giorgio Esposto; Gabriele Giansanti; Irene Mignini; Raffaele Borriello; Gianpaolo Vidili; Antonio Gasbarrini; Maria Elena Ainora; Maria Assunta Zocco (Diagnostics)
Transarterial chemoembolization (TACE) is a well-established treatment for intermediate-stage hepatocellular carcinoma (HCC), shown through randomized trials to improve survival compared to supportive care in patients with large, unresectable tumors who are not candidates for liver transplantation or local ablation. As the most commonly used transarterial intervention, TACE is also employed to downstage advanced HCC, allowing certain patients to become eligible for orthotopic liver transplantation under the Milan criteria. Despite its widespread use, variability in therapeutic outcomes highlights the need for improved procedural guidance. Recent advancements in intra-arterial contrast-enhanced ultrasound (IA CEUS) offer new opportunities to enhance TACE precision with real-time imaging that provides superior visualization of tumor vasculature and chemoembolic agent distribution. This review explores the role of IA CEUS in refining TACE for HCC, emphasizing its potential to increase intraprocedural accuracy and reduce the risk of incomplete tumor embolization. The enhanced spatial resolution of IA CEUS enables real-time tracking of embolic agent dispersion within tumor vessels, which could improve therapeutic efficacy by ensuring complete tumor targeting and minimizing non-target embolization. Additionally, IA CEUS may decrease procedural complications by allowing dynamic adjustment of embolic delivery based on real-time imaging feedback. By reviewing existing evidence on IA CEUS applications in TACE, this article highlights the modality’s potential to transform treatment protocols, improve outcomes, and expand the patient population eligible for TACE.